Ecology of luminous bacteria in penaeid shrimp grow-out systems of West Bengal, India - Abraham, T Jawahar; Gupta, Tapti Sen; Sasmal, Debasis (Indian Journal of Fisheries, 2011)
Occurrence and distribution of luminous bacteria (LB) from improved traditional, stagnant pond, modified extensive and semi-intensive shrimp grow-out systems of West Bengal were studied. About 51% of pond water, 31% of pond sediment and 22% of water samples had detectable level of LB. They were isolated invariably in all the diseased shrimp samples. The highest luminous bacterial counts (LBC) were recorded in the water samples of semi-intensive system (log <2.00 - log 4.70/ml) and sediment samples of modified extensive system (log <3.00 - log 5.00/g). An increase in the average LBC of water from log 2.44 ± 0.62/ ml to log 2.91 ± 0.53/ml up to 60 days of culture was recorded. The counts, however, decreased to log 2.30 ± 0.42/ml towards the end. The total viable bacterial counts were in the range of log 3.42 - log 6.67/ml, with the average of above log 5.00/ml pond water, the highest being in semi-intensive system (log 5.70 ± 0.72/ml). In pond sediment samples, the range of TVC recorded was log 3.70 - log 7.37/g, with the average of above log 6.00/g sediment. The majority of the LB isolated from various farms was V. harveyi (94.86%) followed by V. splendidus biotype 1 (4.57%) and V. fischeri (0.57%). The preponderance of LB in certain shrimp culture systems and the observed shift in the bacterial profile of water from the day of flooding up to 60 days strongly suggests the imbalance shrimp farming can bring about in autochthonous microflora.